Analisis Dan Perancangan Sistem Informasi Pemesanan Produk Pengantin Berbasis Web Pada Wedding Organizer MeyMey Cantik - Jannah, Dian Nur; Mulyono, Herry (Jurnal Manajemen Sistem Informasi, 2021)
Wedding organizer is aservice that workspersonally Helping bride and groom in planning and supervising the implementatition of a series of wedding party in accordance with schedule and budget set. Wedding organizer information system created with utilized web based technology, with the aim to expand the area of promotion and sale of wedding packages and simplify the ordering process. The wedding information system use PHP and MySQL programming, method used in the development of this system is prototyping method which consists of analysis, design, application creation, evaluation dan result. Wedding information system helpful for those do not to bother with planning problem. With the development of technology today wedding organizer start to move from manual process into online proses is wedding information system web based.